Circulating Extracellular Vesicles Carry Immune Regulatory miRNAs and Regulate Vaccine Efficacy and Local Inflammatory Response After Vaccination - Oshiumi, Hiroyuki (Frontiers in Immunology, 2021)
Vaccination is the best prophylaxis for the prevention of infectious diseases, including coronavirus disease 2019. However, the efficacy of vaccines and onset of adverse reactions vary among individuals. Circulating extracellular vesicles (EVs) regulate the immune responses after vaccination by delivering microRNAs (miRNAs) to myeloid and lymphoid cells. Among these, miR-192 levels in serum EVs increase with aging, in an IL-6-dependent manner, reducing excessive IL-6 expression in aged mice, creating a negative feedback loop. Excessive IL-6 expression reduces vaccination efficacy in aged mice, while EV miR-192 improves efficacy in these aged mice as well, making this miRNA an interesting focus of study. miR-21 levels in serum EVs also increase with aging, and regulates the expression of IL-12 required for Th1 responses; therefore, EV miR-21 is expected to regulate vaccine efficacy. miR-451a, another important miRNA, is abundant in serum EVs and controls the expression of cytokines, such as type I interferon and IL-6. However, levels differ among individuals and correlate with local inflammatory symptoms experienced after a seasonal flu vaccination. These findings suggest the importance of EV miRNAs as a tool to improve vaccine efficacy and also as biomarkers to predict the immune response and adverse reactions after vaccinations.